Asymptotic synthesis of contingent claims with controlled risk in a sequence of discrete-time markets - David M. Kreps; Walter Schachermayer (Theoretical Economics, 2021)
We examine the connection between discrete-time models of financial markets and the celebrated Black–Scholes–Merton (BSM) continuous-time model in which ''markets are complete." Suppose that (a) the probability law of a sequence of discrete-time models converges to the law of the BSM model and (b) the largest possible one-period step in the discrete-time models converges to zero. We prove that, under these assumptions, every bounded and continuous contingent claim can be asymptotically synthesized, controlling for the risks taken in a manner that implies, for instance, that an expected-utility-maximizing consumer can asymptotically obtain as much utility in the (possibly incomplete) discrete-time economies as she can at the continuous-time limit. Hence, in economically significant ways, many discrete-time models with frequent trading resemble the complete-markets model of BSM.
Keywords: D0; G0; 330; Market completeness; Black-Scholes-Merton model; synthesis of contingent claims